К вопросу о восстановлении речевой коммуникации при афазии - Пайлозян, Ж. А.
Speech communication disorders appear during the aphasia, that have negative infl uence on the self-est eem, family and social st atus of patients. The ¢ eech communication rest oration depends on the microsocial environment of the patient and his family. The ¢ ecialist s, signifying the role of the family in the process of overcoming aphasia, off er some methods and ways that will help him in ¢ eech communication rest oration. The problem of ¢ eech communication rest oration of people with aphasia is up-to-date and needs further research.
Keywords: Логопедия